FEATURES OF MICROBIOCENOSIS OF THE NASAL MUCOSA AND ITS ROLE IN ALLERGIC DISEASES (LITERATURE REVIEW) - Zukhra N. Orinbayeva; Zuhra A. Nuruzova; Dilnoza A. Shahobiddinova (Central Asian Journal of Medicine, 2025)
In the modern world, allergic respiratory diseases have a huge place among all chronic diseases. The annual increase in the prevalence of allergic rhinitis and bronchial asthma among the global population makes relevant studies underlying their pathogenesis. Changes in the nasal mucosa alter its most important function — protection from aggressive environmental factors — allergens and pollutants. Inflammatory processes in the nasal cavity interfere with the normal mucosa functioning as a non-specific barrier and facilitate their further penetration into the microorganism. This article provides an overview of the current scientific medical literature, summarizing the results of scientific research regarding microbiocenosis of the nasal mucosa and its effect on the development and formation of allergic rhinitis.